2019
DOI: 10.1101/2019.12.27.886135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation across the genome in aged human skeletal muscle tissue and stem cells: The role of HOX genes and physical activity

Abstract: Skeletal muscle tissue demonstrates global hypermethylation with aging. However, methylome changes across the time-course of differentiation in aged human muscle stem cells and larger coverage arrays in aged muscle tissue have not been undertaken. Using 850K DNA methylation arrays we compared the methylomes of young (27 ± 4.4 years) and aged (83 ± 4 years) human skeletal muscle and that of young/aged muscle stem cells over several time points of differentiation (0, 72 hours, 7, 10 days). Aged muscle tissue was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 83 publications
2
13
0
Order By: Relevance
“…(Figure 3a). Promoterassociated dmCpGs in CpG islands were underrepresented compared to CpGs in the whole genome ( Figure 3b, File S1b), which is a confirmation of the results of Zykovich et al 8 , but in contrast to the findings of Turner et al 9 , where most dmCpGs were located in CpG islands. Finally, we found a significant overlap of 2,334 CpGs between the age-related dmCpGs of the present study and the age-related dmCpGs of Zykovich et al (p = 2.2e-16) (Figure 3c, File S1d).…”
Section: More Hypomethylated Cpgs and Upregulated Genes In Previouslysupporting
confidence: 87%
See 2 more Smart Citations
“…(Figure 3a). Promoterassociated dmCpGs in CpG islands were underrepresented compared to CpGs in the whole genome ( Figure 3b, File S1b), which is a confirmation of the results of Zykovich et al 8 , but in contrast to the findings of Turner et al 9 , where most dmCpGs were located in CpG islands. Finally, we found a significant overlap of 2,334 CpGs between the age-related dmCpGs of the present study and the age-related dmCpGs of Zykovich et al (p = 2.2e-16) (Figure 3c, File S1d).…”
Section: More Hypomethylated Cpgs and Upregulated Genes In Previouslysupporting
confidence: 87%
“…However, the investigators were unable to find methylation changes after 12 weeks of RT, probably due to the low sample size, the strict FDR adjustment and the limited number of CpGs tested. We hypothesized that training would reverse the ageing-induced hypermethylation, predominantly found in older muscle tissue in literature 8,9 , based on the hypomethylating effect of aerobic exercise [10][11][12][13] , lifelong physical activity 15 and RT in young to middle-aged adults 13,81 . However, both in young and older muscle tissue we observed that a first training period induced both hypomethylation and hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the overall pattern of age-related DNA methylation changes in muscle showed mixed results, three reporting more hypermethylation with age 7,8,11 and one finding slightly more hypomethylation with age 10 .…”
Section: Discussionmentioning
confidence: 93%
“…Age-related DNA methylation changes in skeletal muscle may be one of the molecular mechanisms underlying sarcopenia, but the full picture is fragmentary. To date, four epigenome-wide association studies (EWAS) 7,8,10,11 have probed age-related DNA methylation changes in the muscle methylome, and both relied on relatively small sample sizes (n=10-50). Studies relying on a small sample size fail to detect small effect sizes and can be prone to large error, so larger initiatives are needed to identify the comprehensive list of CpG loci that change in methylation with age in human skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%